2013
DOI: 10.1108/jhom-11-2012-0225
|View full text |Cite
|
Sign up to set email alerts
|

Tackling disinvestment in health care services

Abstract: Purpose -The aims of this paper are to explore the experiences of budget holders within the English National Health Service (NHS), in their attempts to implement programmes of disinvestment, and to consider factors which influence the success (or otherwise) of this activity. Design/methodology/approach -Between 24 January and 15 March 2011 semi-structured, telephone interviews were conducted with representatives of 12 Primary Care Trusts in England. Interviews focussed on: understanding of the term "disinvestm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 48 publications
2
77
0
Order By: Relevance
“…Disinvestment, is defined as the process of completely or partially withdrawing healthcare resources from currently funded areas that provide little benefit for their cost [7]. Disinvestment can lead to full or partial withdrawal of a technology, contractual variation, restriction, or substitution and employs financial disincentives [5, 8]. De-implementation is defined as the process where the use of low-value care is reduced or stopped on a structural basis in a planned process that uses a set of activities, which can include financial disincentives, but also uses other activities such as data feedback, education, and system interventions [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Disinvestment, is defined as the process of completely or partially withdrawing healthcare resources from currently funded areas that provide little benefit for their cost [7]. Disinvestment can lead to full or partial withdrawal of a technology, contractual variation, restriction, or substitution and employs financial disincentives [5, 8]. De-implementation is defined as the process where the use of low-value care is reduced or stopped on a structural basis in a planned process that uses a set of activities, which can include financial disincentives, but also uses other activities such as data feedback, education, and system interventions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, providers could succumb to pressure from the patient in providing unnecessary tests or treatments. Facilitators to overcome these barriers include the use of KT strategies such as clinical champions to increase buy-in, and providing knowledge of the net benefit to patients if the technology is removed or decreased [2, 5, 8]. Knowledge translation and implementation of HTR recommendations could also be motivated by explicitly stating that the intention is to improve efficiency, patient safety and patient outcomes, rather than cost savings [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between them they identified 78 articles, of which 38 were deemed relevant. Of these: l 16 were descriptive or discursive 83,[301][302][303][304][305][306][307][308][309][310][311][312][313][314][315] l six were on programme budgeting and marginal analysis [316][317][318][319][320][321] l six were surveys of attitudes to disinvestment 302, [322][323][324][325][326] l five related to NICE [327][328][329][330][331] l one analysed a RCT in terms of discontinuation of a particular drug. 332 Four systematic reviews were identified, three of which were concerned with disinvestment.…”
Section: Literature Searchesmentioning
confidence: 99%